Synthetic pectin–cellulose nanofiber capsule recapitulates the mechanical properties of a regenerating plant cell wall - Cyril Grandjean; Ravi Shanker; Sarah A. Pfaff; Anran Mao; Jordi Chan; Sophie Asnacios; Atef Asnacios; Sulin Zhang; Daniel J. Cosgrove; Enrico Coen; Anna J. Svagan; Pauline Durand-Smet (Proceedings of the National Academy of Sciences, 2026)
Plant primary cell walls are dynamic supramolecular assemblies composed of layered cellulose, hemicellulose, and pectin, progressively built through synthesis and secretion. However, the specific architectural features and structural components sufficient to endow the mechanical properties of the wall remain unclear. Here, we construct a minimal synthetic spherical shell and compare its structural and mechanical properties to those of a plant single-cell system. To eliminate complexities from intercellular connectivity and developmental history, we exploit the ability of plant protoplasts to regenerate cell walls de novo. Compression tests of regenerating protoplasts between parallel plates reveal that wall stiffness increases with wall thickening over time. Despite differences in assembly pathways, architecture, and composition, the synthetic shell exhibits a similar thickness-dependent modulus and similar material stiffness. The synthetic shell, mainly composed of pectin and cellulose nanofibers, mirrors the mechanical behavior of regenerating primary cell walls, suggesting that these components play a major role in conferring key mechanical properties in the limit of compressive small deformations. Extending this comparative approach should allow similarities and differences in component interactions in controlling wall behavior to be identified.